Trends in Natural Products 2024, PSE, Young Scientists' Meeting Phytochemical Society of Europe (PSE) (Masaryk University Press, 2024)
The aim of the annual Young Scientists' Meeting was to give doctoral students and postdoctoral fellows the opportunity to meet their experienced senior colleagues, and to present their research to a broad scientific forum. In addition to this, we emphasized personal meetings, creation of (sometimes long-lasting) contacts and the possible networking of students from many countries. More than 150 participants from over 25 countries contributed to Trends in Natural Products 2024, PSE, the Young Scientists' Meeting, and the Phytochemical Society of Europe Book of Abstracts. 24 plenary lectures, 38 oral presentations and 72 posters are summarized in the Book of Abstracts of this symposium.